Probiótico para tilápia nilótica em ambiente de desafio - Figueiredo, Ana Caroline (2020)
The use of probiotics has been an alternative to maximize animal performance byimproving intestinal conditions for the processes of digestion and absorption of nutrients. Thus, the present study aimed to evaluate the inclusion of the probiotic for juvenil